A Dynamic Stochastic Hybrid Model to Represent Significant Wave Height and Wave Period for Marine Energy Representation - Becker-Cares, C; Chavez-Orostica, H; Verdejo-Fredes, H; Acosta-Barbosa, K; Awerkin, A (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
This paper presents a methodology to represent ocean wave power generation based on real data observation for significant wave height (SWH or H s ) and wave period (WP or T). This technique is based on a hybrid model, which considers Fourier series and stochastic differential equations, allowing a continuous time representation of the random changes in the parameters associated with wave power generation (H s and T). The methodology is explained, including estimation methods and a validation procedure. The data series generated by the models erre used to create simulated wave power output applying a transformed matrix and a theoretical model. The results validate the utilization of this technique, when the objective is to obtain a robust dynamic representation of a random process, oriented to linear studies. © 2019 by the authors.